Taxonomical and molecular authentication of the Ceropegia candelabrum L. var. candelabrum (Apocynaceae): A new record from Eastern India - Naskar, Ayan Kumar; Dwari, Saurav; Tripathi, Sayantan; Mondal, Amal Kumar (Plant Science Today, 2024)
Ceropegia candelabrum L. is the lectotype of the genus Ceropegia that is native to the Western Ghats of India. This species is reporting for the first time from West Bengal, which is the eastern bottleneck of India. This species has very attractive, eye-catching flower characteristics viz., corolla-tubular; corolla tube long abruptly dilated at the base, claw is fused forming tube-like structure, corolla limb connate at the tip forming a globular cage. We apply both traditional and advanced methodologies to properly authenticate the newly collected species. However, the taxonomy, as well as the molecular (rbcL, ITS, and rbcL+ITS) data, confirm the identity of that species. Detailed morphology, a new distributional geographic area, and molecular identification are presented here.